The Assassination of John F Kennedy - Collins, Terry (Capstone, 2020)
November 22, 1963 began as a good day for President John F. Kennedy. From the time he got off the plane at Love Field, he was pleasantly surprised to see thousands of admirers who awaited the arrival of Air Force One at Love. As the motorcade traveled from Love Field into the city, people lined the street to catch a glimpse of the popular president and his beautiful and stylish wife. However, a national tragedy would unfold within an hour. This graphic nonfiction book tells the story of this terrible day.